2018
DOI: 10.1016/j.ihj.2016.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in the clinical presentation of endomyocardial fibrosis in India?

Abstract: These differences may have been due to the better nutrition of the Alleppey patients due to a higher exposure to fish compared to the Trivandrum population. Better nutrition would protect against Magnesium deficiency and prevent the absorption of Cerium in the patients from Alleppey, compared to those from Trivandrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Cardiac transplantation was used only occasionally. Although Moraes and colleagues previously reported a 55% chance of survival, a more recent study, Gupta et al have been reported that EMF's survival is 37% at 10 years . Longer survival and arrest in disease progression may occur in patients with early‐diagnosed mild disease and improved socioeconomic status, biventricular involvement (moderate‐severe), and right ventricular fibrosis, and the presence of tricuspid and mitral regurgitation are associated with greater mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac transplantation was used only occasionally. Although Moraes and colleagues previously reported a 55% chance of survival, a more recent study, Gupta et al have been reported that EMF's survival is 37% at 10 years . Longer survival and arrest in disease progression may occur in patients with early‐diagnosed mild disease and improved socioeconomic status, biventricular involvement (moderate‐severe), and right ventricular fibrosis, and the presence of tricuspid and mitral regurgitation are associated with greater mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…No se conoce cuál de estos agentes tiene una relación causa-efecto o si funcionan como un disparador de un proceso latente. Un hecho interesante que apoya las anormalidades nutricionales es el dato presentado por Gupta, et al 9 , demostrando que una dieta enriquecida para prevenir anormalidades del magnesio y del cerio reduce la ocurrencia de la enfermedad. El marcador patológico de la enfermedad es el engrosamiento endocárdico difuso o focal, involucrando ambos ventrículos el 50% de los casos, y en el 40% solo se afecta el ventrículo izquierdo.…”
Section: Discussionunclassified
“…The 10-year survival rate of EMF in most recent publications is 37%. 13 Longer survival can occur in patients with mild disease and early diagnosis; however, biventricular involvement (moderate-severe), right ventricular fibrosis, and the presence of mitral and tricuspid regurgitation are associated with higher mortality rates 14 of up to 75% at 2 years in advanced stages despite pharmacological treatment. 15 …”
Section: Discussionmentioning
confidence: 99%
“…3 The 10-year survival rate of EMF in most recent publications is 37%. 13 Longer survival can occur in patients with mild disease and early diagnosis; however, biventricular involvement (moderate-severe), right ventricular fibrosis, and the presence of mitral and tricuspid The score is assigned according to the severity of atrioventricular regurgitation. ‡ M movement of the interventricular septum refers to a pattern of movement observed on M-mode echocardiography that is thought to be due to obliteration or restriction of the left ventricular apex combined with mitral regurgitation.…”
Section: Video Highlightsmentioning
confidence: 99%